Behaviour of 1-Octadecanethiol Film Spread over Silver Nitrate Solution - Ahmad, Jamil; D. Silavwe, Ned (Asian Journal of Chemistry, 2010)
Force-area isotherm of 1-octadecanethiol over aqueous silver nitrate subphase has been studied. A comparison of this isotherm with that obtained over pure water subphase is of interest, since thiols are known to form complexes with Ag+ in bulk aqueous solutions. As the monolayer over the silver nitrate solution is compressed, at first it behaves as a typically expanded monolayer, and then goes through a less steep region of transition, after which the isotherm becomes identical to that over pure water. This has been interpreted as being caused by the silver part of the complex having been squeezed out of the monolayer into the subphase.